Age changes in pain perception: A systematic-review and meta-analysis of age effects on pain and tolerance thresholds. (April 2017) - Lautenbacher, Stefan; Peters, Jan H.; Heesen, Michael; Scheel, Jennifer; Kunz, Miriam
Highlights: Aging decreases sensitivity for pain of low intensity. Reduced sensitivity is especially apparent for heat pain and for pain applied to the head. Age-related increases in pain thresholds are greatest the wider the age gap between groups. Aging has no strong effect on pain tolerance. Abstract: Demographic changes, with substantial increase in life expectancy, ask for solid knowledge about how pain perception might be altered by aging. Although psychophysical studies on age-related changes in pain perception have been conducted over more than 70 years, meta-analyses are still missing. The present meta-analysis aimed to quantify evidence on age-related changes in pain perception, indexed by pain thresholds and pain tolerance thresholds in young and older healthy adults. After searching PubMed, Google Scholar and PsycINFO using state-of-art screening (PRISMA-criteria), 31 studies on pain threshold and 9 studies assessing pain tolerance threshold were identified. Pain threshold increases with age, which is indicated by a large effect size. This age-related change increases the wider the age-gap between groups; and is especially prominent when heat is used and when stimuli are applied to the head. In contrast, pain tolerance thresholds did not show substantial age-related changes. Thus, after many years of investigating age-related changes in pain perception, we only have firm evidence that aging reduces pain sensitivity for lower pain intensities.